Metacognitive Strategies and Reflective Practices in EFL Writing: Insights From Arab Bedouin Learners in Jordan’s Desert Context - Atef Asri Alkhotaba; Abdul Mutalib Embong; Muhamad Khairul Bin Zakaria; Abdallah Mohammad Almahasneh; Monther Mohammad Aljarrah (Ijaz Arabi Journal of Arabic Learning, 2026)
The purpose of the research was to investigate the impact of metacognitive and reflective thinking skills as a modern teaching method on the dimensions of the basic writing among sixth-graders at a Bedouin school in Jordan, and to measure whether using the Kember’s levels (2008) of reflection which are habitual action, understanding, reflection, and critical reflection can improve students' writing performance. A quasi-experimental research design was employed, and the study consisted of 70 female sixth-grade students from a Bedouin school in Jordan that are divided into two comparable groups (according to their classrooms) as purposive sampling for the academic year 2025. A pretest and a posttest with Analytical Marking Scale and writing rubrics will be conducted on both groups to provide the quantitative data to show the significance difference between the experimental group and the control group in the study. The study indicated that there is a significant difference in the performance of the students’ writing between the experimental and control groups at P 0.000. The‍‌‍‍‌‍‌‍‍‌ results indicate that students in the experimental group, who received reflective thinking treatment, were able to write a better draft than those in the control group, who followed a regular teaching plan without the benefit of reflective thinking. This means that reflective thinking is an effective tool for enhancing writing skills. The research highlights the incorporation of reflective thinking models as a means of overcoming teaching challenges in rural ‍‌‍‍‌‍‌‍‍‌schools.